Effects of temperature and concentration of carrier on the dyeing of polypropylene tape yarn with disperse dyes - Pornchai Chruakanchana (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1990